Lessons from an International e-Learning Project - Breen, Paul (International Review of Research in Open and Distributed Learning, 2007)
This paper offers a critical examination of an e-learning project in the context of a Distance Education training program delivered to teacher trainers in Rwanda. In examining the successes and failures of the project, it uses a framework based on ideas promulgated by Moore (1995) and strives to provide guidance and reference for future projects in this field.